(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2024)
Nanoparticles generated from Calotropis procera leaf extract were compared for their quantity, nature, and antibacterial action in this work. The generated ZnO NPs were examined using FTIR and SEM. Images captured by scanning electron microscopy clearly show that the biologically produced particles have a size between 100 and 200 nm. The minimum inhibitory concentration (MIC) values of several antibacterial agents were determined by conducting studies on both plant and human diseases. The green produced ZnO NPs exhibited strong antibacterial activity against both human and plant pathogens at all doses tested, with the highest zone of inhibition seen at 30 μg/mL. At concentrations ranging from 50 to 12.5 εg/ml of nano-ZnO, all microorganisms tested were entirely inhibited, according to the Minimum Inhibitory Concentrations of NPs against human pathogenic bacteria and plant bacterial pathogens. Various concentrations of ZnO nanoparticles significantly inhibited spore germination, demonstrating the antifungal action of these particles against fungus.